A survey of public central school libraries in the Division of Tarlac 1980-1981 - Sandiko, Nonelia L.; Buenrostro, Juan Jr. C.; Hidalgo, Namnama P. (Quezon City Institute of Library Science, University of the Philippines Diliman, 1981)
This survey was conducted to evaluate the present status of public central school libraries in the Division of Tarlac for the school year 1980-1981 in relation to existing standards.
The study used questionnaires, library visits, interviews and observations in collecting pertinent data on the role of libraries in the curriculum development of the entire educational program.
Findings of this survey indicate that public central school libraries in Tarlac are below standard. Library collections are inadequate and are not organized. Library quarters and facilities are inadequate. They are staffed by part-time teacher-librarians who have little or no training in library science. Standard library services are not provided. There is no regular library budget.
At present, the public central school libraries are not an asset to the educational system. They cannot support the school in achieving the objectives of education. They are important but neglected segment of the entire educational system.
Mimeographed.
Special Problem (Master of Library Science)
Keywords: School libraries -- Philippines -- Tarlac